2020
DOI: 10.1136/jitc-2019-000356
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy to treat malignancy in patients with pre-existing autoimmunity

Abstract: In the past 10 years, immune checkpoint inhibitors (ICIs) have become an additional pillar of cancer therapy by activating the immune system to treat a number of different malignancies. Many patients receiving ICIs develop immune-related adverse events (irAEs) that mimic some features of classical autoimmune diseases. Unfortunately, patients with underlying autoimmune conditions, many of whom have an increased risk for malignancy, have been excluded from clinical trials of ICIs due to a concern that they will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…The current study did not analyze the impact of autoimmune diseases as preexisting autoimmunity may be associated with ICIs efficacy and irAE [38]. However, the previous studies showed ICIs lead to similar rates of irAEs in patients with coexisting autoimmune diseases compared with those without existing coexisting autoimmune diseases [39].…”
Section: Discussionmentioning
confidence: 86%
“…The current study did not analyze the impact of autoimmune diseases as preexisting autoimmunity may be associated with ICIs efficacy and irAE [38]. However, the previous studies showed ICIs lead to similar rates of irAEs in patients with coexisting autoimmune diseases compared with those without existing coexisting autoimmune diseases [39].…”
Section: Discussionmentioning
confidence: 86%
“…In breast cancer, a lower rate of systemic treatment was seen in rural areas [ 54 , 55 ]. Flare of a pre-existing autoimmune disorder is common with ICI treatment [ 56 , 57 , 58 ], but information on patients with autoimmune disorder receiving ICI is only available from retrospective studies, as patients were excluded from clinical trials [ 56 ]. Additionally, in most studies heterogenous autoimmune disorders were summarized.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that patients with preexisting autoimmune diseases had a higher frequency of severe irAEs and new disease symptoms, for some time there were restrictions on the inclusion of these patients in treatment groups [ 121 ]. However, recent retrospective data have demonstrated the safety and efficacy of ICIs in patients with pre-existing AID [ 122 ]. The presence of AID in the anamnesis requires more careful monitoring of the patient’s condition, and the management with specialists in autoimmune pathologies.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%